Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.3323/jcorr1974.39.6_298
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition of Carbon Steel by Lithium Molybdate in Concentrated LiBr Solutions at Elevated Temperatures

Abstract: Inhibition of the corrosion of carbon steels by lithium molybdate in bellow 21.4mol/kg-H20 alkaline lithium bromide aqueous solution was investigated in glass sealed tube at various temperatures.Lithium molybdate gives an excellent corrosion inhibition for carbon steel even at a concentration as low as 0.003mol/kg-H20 in the presence of 0.36mol/kg-H20 lithium hydroxide.In addition, this inhibitor is effective in the temperature range from 373 to 473K. It is concluded that the corrosion inhibition action by lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Test solutions as described below were prepared by dissolving reagent grade chemicals of LiBr•H 2 O, LiOH•H 2 O and Li 2 MoO 4 into deionized water at about 333 K 1,4) (hereafter, % represents mass%);…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Test solutions as described below were prepared by dissolving reagent grade chemicals of LiBr•H 2 O, LiOH•H 2 O and Li 2 MoO 4 into deionized water at about 333 K 1,4) (hereafter, % represents mass%);…”
Section: Methodsmentioning
confidence: 99%
“…Tanno et al 4) reported that the surface of the carbon steel after immersion for 720 ks was covered with a film and corrosion was suppressed. On the other hand, the present research measured the polarization curves of the specimen after immersion in the solution for a short time of 0.3 ks.…”
Section: Effect Of Temperature On Cathodic Current Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Molybdate induces passivation of steel in an alkaline LiBr solution but does not cause pitting as chromate 8) 10) and nitrate 2), 8) do. It was revealed that molybdenum oxide layer is formed on the outer side of the surface film on steel as a result of reduction of molybdate 5) . Yashiro et al 7) reported film formation kinetics on carbon steel in the concentrated LiBr solutions containing LiOH and Li 2 MoO 4 .…”
mentioning
confidence: 99%
“…2), it took about 40 h for the Fe electrode to rise in potential. The concentration of molybdate of the order of 10 3 mol/kg is regarded as acceptable for steady running of commercial adsorption refrigerators 5) . However, the initial passivation process does not seem fast enough at this concentration because the evolution of hydrogen could deteriorate the performance of the refrigerator.…”
mentioning
confidence: 99%